Construction and immunogenicity in a prime-boost regimen of a Semliki Forest virus-vectored experimental HIV clade A vaccine. - Hanke, T; Barnfield, C; Wee, E; Agren, L; Samuel, R; Larke, N; Liljeström, P (2003)
A novel, experimental subunit human immunodeficiency virus (HIV) vaccine, SFV.HIVA, was constructed. This consists of Semliki Forest virus (SFV), which is a suitable vaccine vector for use in humans, and a passenger gene encoding HIVA, which is an immunogen derived from HIV-1 clade A that is being currently tested in clinical trials of combined DNA- and modified vaccinia virus Ankara (MVA)-vectored vaccines in Oxford (UK) and Nairobi (Kenya). In the mouse, the SFV.HIVA vaccine was highly immunogenic for T cell-mediated immune responses and induced T cell memory that lasted for at least 6 months. SFV.HIVA was also compared to the vaccines currently used in the clinical trials and was shown to be as effective in T cell induction as pTHr.HIVA DNA but less immunogenic than MVA.HIVA. When tested in a prime-boost regimen, SFV.HIVA-induced responses could be boosted by MVA.HIVA. This work is a part of a long-term effort to build a panel of subunit vaccines expressing a common immunogen, which will allow both a direct comparison of various vaccine vectors and combined vaccination regimens in humans and provide more flexibility and/or a potential optimization of vaccinations for individuals based on their pre-existing anti-vector immunity.